Study guides

☆☆

Q: If x equals 2 and y equals 9 then 7x plus 3y equals?

Write your answer...

Submit

Related questions

x+7x+3y-y =8x+2y =2(4x+y)

(14x-2y)+(7x-3y)+(-3x) = 14x-2y+7x-3y-3x =(14+7-3)x-(2+3)y =18x-5y

7x + 3y = 14 5x + 9y = 10 __________ (subtract bottom from top) 2x -6y = 4, therefore 2x = 4 + 6y, therefore x = 2 + 3y Insert x = 2 + 3y into the original equation and calculate 7(2 + 3y) +3y = 14 14 + 21y +3y = 14 24y = 0 y = 0 If y= 0, then x = 2 FINAL ANSWER!

5x - 3y -7x + 2y +3x = (5-7+3)x + (-3+2)y = x - y

1. 4x + 3y = -22. x - y = -4Multiplying 2. by 3 gives: (we have done this so that we end up with a -3y)3. 3x - 3y = -121. added to 3. gives: (now, by adding, the 3y & -3y will cancel out)4. 7x = -14 (the 4x + the 3x gives 7x, the y's cancel out, -2 + -12 gives -14)thus x = -14/7x = -2Substituting x = -2 into 1. gives(4 * -2) + 3y = -2-8 + 3y = -23y = -2 + 83y = 6y = 2Thus x = -2 and y = 2.

-4(7x-3y-z)-(-6)(9x-z+2)

7(3y-2)-(-4y+9)

7x + 2 = 6x + 2 if and only x = 0.

7x + 2 = 5,6

(1) 5x+y=-12 (2) 7x-3y=-30 From (1) one gets y = -12-5x Put into (2) 7x-3y = 7x -3 (-12-5x) = 7x + 36 +15 x = 22x +36=-30 22x = -30-36 = -66 so x = -3 and y=-12-5x = -12-5x-3= 3 The solution is (-3,3)

X=4.2666666666667

(3y + 5)(y - 2)

5y-2y= 3y+2 5y-2y-3y= 2 0y= 2

2x-3y=13

-7x + 5 = -9 -7x = -14 7x = 14 x = 2

Subtract by 7x and divide by 2.

7x+2-2=16-27x = 147x/7 = 14/7x = 2

7x is still the slope, no matter what x equals.

(2, 2)

5x+2x-3y+y = (5+2)x+(-3+1)y = 7x - 2y

y=8

y=2

y = -1

x = -5

(-1, 0)